Answer:
![y+1=\frac{-2}{3} (x+4)](https://tex.z-dn.net/?f=y%2B1%3D%5Cfrac%7B-2%7D%7B3%7D%20%28x%2B4%29)
Step-by-step explanation:
you can use the equation point-slope of a line
(y-y1)= m(x-x1)
m is the slope =rise /run
to get from the lower point on the line to the other you rise 4 units and run -6 units so m= -4/6= -2/3
now that you have the slope pick you need one point
pick any poin on the line for example (-4, -1)
now you substitute into the point-slope equation point (-4,-1) and slope -2/3
(y+1)= -2/3(x+4)
in standard form will be
y=![\frac{-2x}{3} -\frac{2*4}{3} -1](https://tex.z-dn.net/?f=%5Cfrac%7B-2x%7D%7B3%7D%20-%5Cfrac%7B2%2A4%7D%7B3%7D%20-1)
y=![\frac{-2x}{3}- \frac{5}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B-2x%7D%7B3%7D-%20%5Cfrac%7B5%7D%7B3%7D)